Characteristics associated with virologic failure in high-risk HIV-positive participants with prior failure: a post hoc analysis of ACTG 5251. Issue 4 (3rd July 2016) - Robbins, Gregory K.; Cohn, Susan E.; Harrison, Linda J.; Smeaton, Laura; Moran, Laura; Rusin, David; Dehlinger, Marjorie; Flynn, Theresa; Lammert, Sara; Wu, Albert W.; Safren, Steven A.; Reynolds, Nancy R.
Abstract : Patients with prior virologic failure (VF) are at an increased risk of subsequent failure, emergence of resistance, and death. This analysis identifies outcomes and correlates of VF in a high-risk population. Methods: A5251 was designed to evaluate an enhanced adherence counseling intervention delivered by nurses from a central call site on virologic suppression. Due to slow enrollment, the study was closed prematurely and revised study endpoints were evaluated (week 24 VF (HIV-1 RNA ≥200 copies/ml) and non-perfect adherence (<100% self-reported using both the ACTG adherence questionnaire and visual analog scale (VAS)). Results: Fifty-nine participants were enrolled, 43 (73%) black non-Hispanic and 23 (39%) women. Median prior antiretroviral regimen changes were three and the co-morbidity in this population was higher than typical for HIV clinical trials. At week 24 ( n = 41), 24 (59%) failed to reach virologic suppression (HIV-1 RNA <200 copies/ml) and 25 (63%) reported non-perfect adherence. Higher depression (CES-D10) and adverse illness perceptions (IPQ-B) were associated with week 24 non-adherence. Early clinical assessments (week 12 HIV-RNA ≥200 copies/mL and non-perfect adherence) as well as higher depression and adverse illness perceptions were associated with week 24 VF. Discussion: In this high-risk population, the proportion of participants with suboptimal adherence and VF was unacceptably high. Interventions to address this treatment gap are clearly needed. Depression and a higher illness perception score, failure to achieve virologic suppression by week 12, and less than perfect adherence could be used to target individuals for early interventions in treatment-experienced, high-risk individuals at high risk for VF.